A cluster of acidic residues in the cytoplasmic domain of SARS-CoV-2 Spike is required for virion-incorporation and infectivity - Charlotte A. Stoneham; Rajendra Singh; Amalia De Leon; Petra Tafelmeyer; Francisco Acosta; Angus Fuori; Michael Anderson; Peter W. Ramirez; Hannah S. Schwartzer-Sperber; Satish Pillai; Mary K. Lewinski; John Guatelli (PLoS ONE, 2026)
Like all coronaviruses, the infectivity of SARS-CoV-2 virus particles (virions) requires incorporation of the Spike glycoprotein. Yet, the mechanisms that support the virion-incorporation of Spike are incompletely defined. We noted an unusual feature of human sarbecovirus Spike proteins: their cytoplasmic domains (CDs) contain a stretch of acidic amino acids (DEDDSE). This sequence resembles a cluster of acidic residues, or acidic cluster (AC) motif, found in the cytoplasmic domain of the cellular endoprotease Furin. In Furin, the acidic cluster acts as a protein sorting signal, supporting its intracellular localization at the trans -Golgi network (TGN). We tested the contribution of the acidic cluster motif in the Spike CD to protein interactions and to the infectivity of SARS-CoV-2. We used virus-like particles (VLPs) as a model for viral “infection” (transduction). The SARS-CoV2 VLPs were produced by co-expressing Spike (S), Membrane (M), Envelope (E) and Nucleocapsid (N) proteins and deliver an RNA encoding luciferase to target cells expressing the ACE2 receptor. Remarkably, when all five acidic residues of the DEDDSE sequence were replaced with alanines, the VLPs were rendered non-infectious. The N-terminal DE residues provided most of the activity of the acidic cluster. These virologically-impaired Spike mutants were able to reach the cell surface and induce the formation of syncytia, indicating that they are fusogenic and capable of anterograde traffic through the biosynthetic pathway to the plasma membrane. Despite this, they failed to efficiently incorporate into virions. We observed acidic cluster motif-dependent interactions of the Spike CD with several cellular proteins that could potentially support its role in virion-incorporation, including the ERM proteins Ezrin, Radixin, and Moesin; the retromer subunit Vps35, and the medium subunits of the clathrin adaptor complexes AP1 and AP2. While the key cofactor and mechanism of action remains to be defined, this region of acidic residues in the Spike CD appears to be a novel determinant of SARS-CoV-2 infectivity.